Description of Leadership in the Service of Youth and Sport Tourism the City of Gorontalo - Rollyn Sofyan Daud; Muh. Firyal Akbar; Rusly Abdurrahman Idji (Journal of Public Representative and Society Provision, 2021)
The good and right leadership is one of the important things in advancing the organization. Good leadership is shown from the capability and ability to control who they lead. This study aims to obtain a description of the description of leadership in the Department of Youth Tourism and Sports in the City of Gorontalo. The research method uses a qualitative approach to the type of descriptive research. Data collection techniques were carried out through interviews with several informants and observations and recording secondary data through searching for documents related to this research. The results of the study concluded that the Leadership in the Department of Youth Tourism and Sports in Gorontalo City was not optimal. This can be seen from the ability to make decisions, the ability to motivate, communication skills and ability to control subordinates.